T cell subpopulations in inflammatory bowel disease: evidence for a defective induction of T8+ suppressor/cytotoxic T lymphocytes. - Goronzy, J (1985)
Abnormal immune responses associated with inflammatory bowel disease may reflect a defect in immunoregulatory functions. To analyse T-T cell cooperation, we examined the influence of polyclonal activation with the mitogen phytohaemagglutinin on the distribution of the T4+ helper/inducer and the T8+ cytotoxic/suppressor T cell subset. Compared to controls, lymphocytes from patients with Crohn's disease displayed a slight reduction in T3+ cells; neither in patients with ulcerative colitis nor in patients with Crohn's disease a significant difference in T4+ and T8+ cells and the T4/T8 ratio was observed. Phytohaemagglutinin stimulation of normal lymphocytes resulted in a decrease of the T4 subset and a clear increase of the T8 subpopulation. In contrast, the subset distribution pattern was not changed by the mitogenic stimulation in any of the patients. This abnormal reaction pattern could not be influenced by the addition of interleukin-2. Small numbers of normal lymphocytes, however, were able to restore the predominant proliferation of T8+ cells. Thus, the reduced response of T8+ lymphocytes cannot be attributed to an altered composition of this subset in patient with inflammatory bowel disease; our results provide evidence for a defective induction of T8+ suppressor/cytotoxic T cells, which is independent from disease activity.